(untitled) (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2024)
This research aims to determine the influence of Readiness for Understanding and Management on the Implementation of Financial Reports Based on Financial Accounting Standards for Micro, Small and Medium Entities in Micro, Small and Medium Enterprises in Kota Baru Jambi. This research uses quantitative methods with primary data which is the result of observations using questionnaires in Kotabaru Jambi sub-district. This research used a sample of 91 respondents. This sampling used a purposive sampling method.